Answer:
Please what are you trying to say
Let s represent the length of any one side of the original square. The longer side of the resulting rectangle is s + 9 and the shorter side s - 2.
The area of this rectangle is (s+9)(s-2) = 60 in^2.
This is a quadratic equation and can be solved using various methods. Let's rewrite this equation in standard form: s^2 + 7s - 18 = 60, or:
s^2 + 7s - 78 = 0. This factors as follows: (s+13)(s-6)=0, so that s = -13 and s= 6. Discard s = -13, since the side length cannot be negative. Then s = 6, and the area of the original square was 36 in^2.
It is 25-6 7 :) that gonna be right
1. (-4)^-6 * (-4)^7 = (-4)^(-6+7) = (-4)^1 =
B. -4
2. (3*10^6)*(8*10^-4) = (3*8)*10^(6-4) = 24*10^2 =
B. 2.4*10^3
Hi, The Answer is:
2x/9
Steps:
Simpilfy the expression:
6x/27
Then reduce the fraction with 3:
2x/9
That's your answer have a good day.